Natural‐Product‐Inspired Aminoepoxybenzoquinones Kill Members of the Gram‐Negative Pathogen Salmonella by Attenuating Cellular Stress Response. Issue 47 (26th October 2016) - Mandl, Franziska A.; Kirsch, Volker C.; Ugur, Ilke; Kunold, Elena; Vomacka, Jan; Fetzer, Christian; Schneider, Sabine; Richter, Klaus; Fuchs, Thilo M.; Antes, Iris; Sieber, Stephan A.
Abstract: Gram‐negative bacteria represent a challenging task for antibacterial drug discovery owing to their impermeable cell membrane and restricted uptake of small molecules. We herein describe the synthesis of natural‐product‐derived epoxycyclohexenones and explore their antibiotic activity against several pathogenic bacteria. A compound with activity against Salmonella Typhimurium was identified, and the target enzymes were unraveled by quantitative chemical proteomics. Importantly, two protein hits were linked to bacterial stress response, and corresponding assays revealed an elevated susceptibility to reactive oxygen species upon compound treatment. The consolidated inhibition of these targets provides a rationale for antibacterial activity and highlights epoxycyclohexenones as natural product scaffolds with suitable properties for killing Gram‐negative Salmonella. Abstract : Aminoepoxycyclohexenones inhibit the growth of Gram‐negative Salmonella in the low micromolar range. The bacterial targets of these antibiotics were analyzed by quantitative ABPP, which revealed a link to bacterial stress response that was validated by various assays. Aminoepoxybenzoquinones were thus validated as natural product scaffolds with suitable properties for the growth inhibition of Salmonella .